Evolución de las distintas generaciones de sistemas adhesivos usados en odontología restauradora - Revisión bibliográfica - Palacios Vásquez, Dario Javier (2023)
Based on the studies conducted by Buonocore in 1955 with the use of phosphoric acid to condition dental enamel, adhesive dentistry had its origin and taking this moment as a starting point, and taking this moment as a starting point, adhesive systems have evolved in order to satisfy the new needs that the dental community has been demanding of them. For the present investigation, the eight different generations of adhesive systems that exist nowadays will be taken into account, where, through a descriptive analytical methodology and the bibliographic review of different scientific articles, the advantages, disadvantages, clinical applications, components and mechanisms of action presented by each of these generations will be announced, as well as a comparative of them, in order to serve as a guide for the reader interested in the subject. The results show that the first three generations of adhesive systems have the most disadvantages and have limited clinical uses, from the fourth generation onwards, the adhesives have several uses, being able to bond composites, ceramics and metals, and have advantages that facilitate clinical practice. Finally, it is deduced that each generation has its own union mechanism, except for the eighth generation known as universal adhesives, which can be used with more than one mechanism. Keywords: Adhesive systems, evolution, generations.